Insecticide Resistance Management: A Detailed Review - Shudeer; Balaji, B. N.; Pandit (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Insecticide resistance poses a significant threat to global agricultural practices, a threat to food security and economic stability. This resistance diminishes the effectiveness of chemical control methods, leading to increased pest infestations, higher production costs and environmental harm. Key resistance mechanisms include metabolic resistance, target site mutations, reduced penetration and behavioural changes. Factors such as high reproductive rates, short generation times and intense selection pressures further accelerate the spread of resistance within pest populations. Effective management strategies, including Integrated Pest Management (IPM), emphasize the importance of combining chemical, biological, and cultural control methods. This review emphasizes the necessity of continuous monitoring, education, and research to develop sustainable pest management solutions. Exploring recent studies and practical examples provides insights into overcoming the challenges posed by insecticide resistance and ensuring the sustainability of agricultural practices.